PENERAPAN STANDART OPERATIONAL PROCEDURE MAKE UP ROOM PADA MASA PANDEMI COVID-19 DI HOTEL FOX HARRIS PEKANBARU - Ahmad Rizki Fauzan; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
During Covid-19 pandemic, the hospitality world received a very large negative impact on the rules for reducing activities outside the home which caused the decline in the income of various hotels in Indonesia. Hotel Fox Harris Pekanbaru is a four-star international class hotel that implements various kinds of service procedure innovations in tackling situations such as those that occur due to the presence of the Covid-19 virus, by implementing a system of strict health protocol rules to maintain maximum and guaranteed service to guests. This study aims to find out what health protocols are implemented in standard operating room cleaning procedures during the Covid-19 pandemic. This study uses a qualitative descriptive method to analyze the problem based on data collection techniques in the form of observation, in-depth interviews, and documentation. The results of this study can be concluded that the Hotel Fox Harris Pekanbaru has implemented standard operating procedures for cleaning rooms that are effective in preventing the spread of the corona virus accompanied by strict health rules. Keywords: Hotel, (SOP) Make Up Room Hotel Fox Harris Pekanbaru